2013
DOI: 10.1186/1556-276x-8-249
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanolayer and nanocluster coatings induced by heat treatment and evaporation technique

Abstract: The paper is focused on the preparation and surface characterization of gold coatings and nanostructures deposited on glass substrate. Different approaches for the layer preparation were applied. The gold was deposited on the glass with (i) room temperature, (ii) glass heated to 300°C, and (iii) the room temperature-deposited glass which was consequently annealed to 300°C. The sheet resistance and concentration of free carriers were determined by the van der Pauw method. Surface morphology was characterized us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 26 publications
2
32
0
Order By: Relevance
“…The overall decrease in friction with increasing tip radius thus cannot be explained by a decrease in adhesion. On the other hand, AFMbased topographical studies of thermal evaporation of gold on SiO 2 have revealed that gold coating at low thickness values (<20 nm) leads to the formation of globular structures on the surface and therefore, a rough topography when compared with thicker coatings (>30 nm) which have more uniform and smoother distribution of gold over the surface 25 . As a smoother tip surface on the nanometer scale would contribute to a reduction in the overall roughness of the tip-sample interface, we tentatively attribute the observation of decreasing overall friction with increasing tip size in our experiments to this effect.…”
Section: Resultsmentioning
confidence: 99%
“…The overall decrease in friction with increasing tip radius thus cannot be explained by a decrease in adhesion. On the other hand, AFMbased topographical studies of thermal evaporation of gold on SiO 2 have revealed that gold coating at low thickness values (<20 nm) leads to the formation of globular structures on the surface and therefore, a rough topography when compared with thicker coatings (>30 nm) which have more uniform and smoother distribution of gold over the surface 25 . As a smoother tip surface on the nanometer scale would contribute to a reduction in the overall roughness of the tip-sample interface, we tentatively attribute the observation of decreasing overall friction with increasing tip size in our experiments to this effect.…”
Section: Resultsmentioning
confidence: 99%
“…Table shows that at least a 100 °C temperature annealing is needed to induce the complete dewetting process of thin (10 nm) metal films. Also for ultrathin metal films (<10 nm) thermal processes at temperature higher than the room temperature is needed . This in contrast with, for example, polymeric films on surfaces where the film dewetting process can be observed, in some, cases at room temperature or temperature little higher than the room temperature .…”
Section: Thin Metal Films Dewetting As Nanofabrication and Patterningmentioning
confidence: 99%
“…Spinodal‐like dewetting can be readily observed in ultrathin (<10 nm) liquid films where the height fluctuations can be of very high percentage with respect the film thickness and where the narrow band of wavelengths can easily grow, leading to film rupture . The dewetting process of ultrathin (<10 nm) metal films is particularly interesting both from scientific and technological point of views . From a basic scientific point of view, ultrathin metal films allow to study some physical peculiarities of the dewetting process so as the atom–atom interaction: for an ultrathin metal film on an inert substrate the film thickness‐dependent intermolecular forces consist of a long‐range attractive part, and a short‐range repulsive part .…”
Section: Thin Metal Films Dewetting As Nanofabrication and Patterningmentioning
confidence: 99%
“…In the XRR method, the recorded diffraction peaks are correlated with the thickness of the examined layer. The other often used methods are: scanning force microscopy [8], atomic force microscopy [9] and ellipsometry [10].…”
Section: Theory Concerning Measurement Of Nanolayer Thicknessmentioning
confidence: 99%